Survey Of Students Learning Interest in Basketball at SMA Negeri 3 Sentani - Ansar CS; Eka I Putu Eka Wijaya Putra; Baharuddin Hasan; Syahruddin Syahruddin; Muh. Syaiful Syam; Daniel Womsiwor (PT Mediatama Zayna Indonesia, 2024)
The aim of this research is to determine students' interest in basketball at SMA Negeri 3 Sentani. This research method uses a survey method by giving questionnaires (Questionnaire) to students using descriptive survey research because it describes the condition of the respondents. The sample for this research was a total population of 150. The results of the research were 12 or 18% of students who played diligently and actively to become professional basketball players. As many as 72 students or 45% were interested in playing basketball for health purposes, while 17 students or 11% were motivated by social encouragement, and 41 students or 23% played basketball just for fun. The learning aspect of basketball students averages 75% because the personal aspect is obtained from the percentage results for each sub-variable using value intervals and number of students.